Prevalence of irritable bowel syndrome and its association with perceived stress level at the International Islamic University Malaysia among nursing students - Mohammed Abdullah Al-Mahmood, Sinan; Rahim, Hamizah; Othman, Noratikah; Ibrahim, Wisam Nabeel (IIUM Press, 2018)
Objective: This study aims to determine the prevalence of irritable bowel syndrome (IBS) and its association with perceived stress levels among nursing students at the International Islamic University Malaysia. Methods: A cross-sectional design was used in this study. A three-part questionnaire was used to gather data on stress levels and IBS symptoms. Part A posed questions on socio-demographic aspects. In part B, a Perceived Stress Scale was used to measure individuals’ perceived stress. Part C used a questionnaire developed by the World Gastroenterology Organisation (WGO) with the support of Danone. Results: The response rate was 85.5%: out of 200 students, 171 completed the questionnaires. According to the results, there is a significant relationship between stress levels and IBS (p = 0.006), where students who experienced moderate stress (151, 88.3%) were more exposed to IBS (60, 39.7%). There is no association between the characteristics of subjects with IBS and their level of stress (P > 0.05). Conclusion: The prevalence of IBS among the students in this study was roughly moderate. The frequency of moderate stress levels was high and there was a significant association with IBS. On the other hand, subject characteristics, e.g. smoking habits, were insignificantly associated with IBS and stress level (SL).